What Are The Main Factor for Improvement in Maintaining Quality Performance at Halal Food MSME? - Putra, Wira Pramana; Rahman, Mila Safira; Afiasri, Amalina Filzah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The Indonesian halal market is increasingly showing significant developments as evidenced by the spending on halal food consumption from Indonesian consumers which is always increasing from year to year. Halal food is an obligation for Muslims, so supply chain integration is needed to ensure that the entire process from upstream to downstream is maintained. and halal status of food products. The Bandung City is one of the highly developed priority cities for halal tourism in Indonesia, therefore insight is needed for halal food MSME owners in determining the factors that affect quality performance, with the hope of achieving food integrity, food safety status. This research is a quantitative research, with data sources obtained through distributing questionnaires online to 100 MSME food owners in the Bandung City. The analysis used is IPMA in order to be able to provide suggestions for improving managerial priorities in maintaining the continuity of quality performance. The results obtained are that the information integrity construct is the variable that has the highest performance level, so that halal food MSMEs in Bandung can improve information integrity in maintaining consistent quality performance. Furthermore, halal production integrity is the variable that has the lowest level of performance. Therefore, halal MSMEs in Bandung City can choose the halal production integrity as a top priority in order to improve the quality performance of MSME halal food in Bandung City.